Regeneration status and floristic composition at pioneer stands on reclaimed ex-coal mine sites in South Sumatra, Indonesia - ARIEF JUNIARTO; SURYO HARDIWINOTO; ENY FARIDAH; IRDIKA MANSUR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Juniarto A, Hardiwinoto S, Faridah E, Mansur I. 2025. Regeneration status and floristic composition at pioneer stands on reclaimed ex-coal mine sites in South Sumatra, Indonesia. Biodiversitas 26: 3446-3459. Understanding the role of pioneer species is crucial for optimizing post-mining reclamation and supporting biodiversity. Therefore, this study aimed to evaluate and compare the regeneration status and floristic composition of pioneer stands at different ages within a reclaimed coal mine site in Tanjung Enim, South Sumatra. By using nested plot sampling, diversity was assessed through Important Value Index (IVI), species richness, Shannon-Wiener Index (H'), and Pielou Evenness Index (J'). The results showed regeneration patterns: Melaleuca cajuputi dominated seedling (IVI: 93.3-200.0%) and sapling stages (IVI: 141.3-200.0%) in all stands, while E. cyclocarpum dominated pole (IVI: 70.4-273.5%) and tree stages (IVI: 229.7-252.5%) in older stands. M. cajuputi supported 10 naturally regenerating species, slightly more than the 9 found in E. cyclocarpum stands. Across both stands, Acacia mangium and Pterospermum javanicum dominated sapling, pole, and tree stages, whereas Commersonia bartramia dominated exclusively in M. cajuputi stands. The community exhibits low to moderate diversity and moderate uniformity (H’: 0.57-1.34; J’: 0.46-0.69). The complementary roles of M. cajuputi in early recruitment and E. cyclocarpum in structural growth promoted ecosystem recovery. Regeneration is successful, but ecological recovery is limited by low diversity and dominance of a few species.